The syntheses, structures and spectroelectrochemical properties of 6-oxo-verdazyl derivatives bearing surface anchoring groups. Issue 5 (19th January 2022) - Kumar, Varshini J.; Wu, Jian-Zhong; Judd, Martyna; Rousset, Elodie; Korb, Marcus; Moggach, Stephen A.; Cox, Nicholas; Low, Paul J.
Abstract : The electronic properties of 6-oxo-verdazyl radicals are tuned by substituents at the 1- and 5-positions, with frontier orbital analysis indicating that each system should display constructive quantum interference in a molecular junction. Abstract : A series of 6-oxo-verdazyl radicals functionalised at the 1- and 5-positions by tolyl, thioanisole and iodophenyl groups were synthesised using conventional strategies. Facile Sonogashira cross-coupling reactions of terminal alkynes with the diiodo derivative were used for synthetic elaboration of the verdazyl core structure with π-conjugated ethynyl groups. The radicals were characterised by EPR spectroscopy, single-crystal X-ray diffraction, cyclic voltammetry and optical spectroscopy. The chemically and electrochemically reversible oxidation and reduction of these radicals within a convenient redox window permitted further studies on the closed-shell cationic and anionic forms using spectroelectrochemical methods, supported by (TD-)DFT calculations.